Kajian Alih Fungsi Lahan Pertanian Ke Non-Pertanian di Kecamatan Junrejo, Kota Batu - Putri, Atha Wina Clarissa; Suharto, Eko; Sugiasih, Sugiasih (Widya Bhumi, 2024)
Development that continues to increase, especially in the housing sector and tourism industry in Junrejo District, Batu City, East Java Province, has resulted in massive land conversion activities occurring, especially the reduction of agricultural land to non-agricultural land. It turns out that some of the land conversions are not in accordance with the regional spatial planning (RTRW) that has been determined. This study aims to determine the suitability of land conversion to RTRW directions in the Junrejo District area and the factors that influence the occurrence of land conversion. The method used in this research is a quantitative method with a spatial approach and a descriptive qualitative method. The results of this research are: (1) there is suitability for land conversion to the RTRW covering an area of 54.47 hectares, nonconformity covering an area of 24.77 hectares, and supporting the RTRW direction covering an area of 104.78 hectares; (2) factors causing land conversion in Junrejo District are the need for housing, increasing land prices, and the choice to work outside the agricultural sector. Pembangunan yang terus meningkat terutama pada sektor perumahan dan industri pariwisata di Kecamatan Junrejo, Kota Batu Provinsi Jawa Timur, membuat aktivitas alih fungsi lahan masif terjadi, terutama penyusutan lahan pertanian ke non pertanian. Ternyata sebagian alih fungsi lahan tersebut tidak sesuai  dengan Rencana Tata Ruang Wilayah (RTRW) yang sudah ditetapkan. Kajian ini bertujuan untuk mengetahui kesesuaian alih fungsi lahan terhadap arahan RTRW di wilayah Kecamatan Junrejo dan faktor-faktor yang mempengaruhi terjadinya alih fungsi lahan tersebut. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan pendekatan spasial dan metode kualitatif deskriptif. Hasil dari penelitian ini adalah: (1) terdapat kesesuaian alih fungsi lahan terhadap RTRW seluas 54,47 hektar, ketidaksesuaian seluas 24,77 hektar dan mendukung arahan RTRW seluas 104,78 hektar; (2) faktor penyebab terjadinya alih fungsi lahan di Kecamatan Junrejo adalah kebutuhan tempat tinggal, harga lahan yang meningkat, dan pilihan bekerja di luar sektor pertanian.